PENGARUH PEMBERIAN TERAPI RELAKSASI AUTOGENIK TERHADAP KADAR GLUKOSA DARAH DAN TEKANAN DARAH PADA PENDERITA DIABETES MELLITUS TIPE II DENGAN HIPERTENSI - Risa irmayanti; Mustayah -; Abdul Hanan (Poltekkes Kemenkes Malang, 2019)
Diabetes mellitus is one of the trigger factors of hypertension. Handling diabetes mellitus type 2 with hipertension one of them is relaxation technique. Physiologically, relaxation can reduce stress. With relaxation the hypothalamus will regulate and decrease the activity of the sympathetic nervous system. The purpose of this study was to determine the effect of autogenic relaxation on blood glucose levels and blood pressure in people with type 2 diabetes mellitus with hypertension. This research uses Pre Experimental Design using one group pretest posttest design. he researchers used consecutive sampling technique with a large sample of 15 respondents who were given the same treatment and measurement (pre post). The result of this research with Paired T test on treatment got p value is 0,000, which means there is effect of autogenic relaxation technique on blood glucose level and blood pressure in people with type 2 diabetes mellitus with hypertension. Expected nurses can apply nonfarmakologis therapy such as autogenic relaxation techniques as a pendampig of pharmacological therapy decreased blood glucose levels and blood pressure in people with type 2 diabetes mellitus with hypertension.